The clinical differences between cough variant asthma cells and humoral immunology indicators: CVA cells and humoral immunology indicators differences - Jin, Lei; Gong, Hua; Zhang, Qinqin (Cellular and Molecular Biology, 2022)
The Purpose of this study was to study and analyze the clinical differences between cough variant asthma (CVA) cells and humoral immunology indicators. For this aim, 73 sick children with CVA were enrolled in this study and were admitted to the Pediatric Inpatient Department of Weifang Maternal and Child Health Hospital for treatment from April 2019 to May 2021. They were divided into the attack stage group (n=45) and the remission stage group (n=28). Meanwhile, 30 children with normal physical examination results were selected as normal controls. Differences in serum levels of TNF-, hs-CRP, IL-4, IL-5, IL-6 and IL-13 were compared among the three groups, as well as the differences in humoral immunology indicators such as T lymphocyte subsets CD3+, CD4+, CD8+, CD4+/ CD8+ and IgA, IgG, IgG, IgM, IgE, IgE and IgG subtypes. Results showed that serum levels of TNF-α and hs-CRP were significantly higher in the attack stage group than those in the remission stage group and normal control group, and the difference was statistically significant (P<0.05). The serum levels of TNF-α and hs-CRP were higher in the remission stage group than those in the normal control group, and the difference was not statistically significant (P>0.05). Serum levels of IL-4, IL-5, IL-6 and IL-13 were significantly higher in the attack stage group than those in the remission stage group and normal control group, and the difference was statistically significant (P<0.05). CD4+ and CD4+/CD8+ were significantly higher in the attack stage group than those in the remission stage group and normal control group, and the difference was statistically significant (P<0.05). The difference in serum levels of IgG1, IgG2 and IgG3 was not statistically significant (P>0.05) among the three groups. While the level of IgG4 subsets in the attack stage group was significantly higher than that in the remission stage group and normal control group, and the difference was statistically significant (P<0.05). Then the cytokines, cells and humoral immunology indicators of CVA patients are not in their normal range. They are involved in the pathogenesis of CVA. The combined detection is of great clinical significance in the diagnosis of early CVA to avoid misdiagnosis and missed diagnosis.